Protective effect of mangrove (Rhizophora apiculata) leaves extract in shrimp (Penaeus monodon) larvae against bio-luminescent disease-causing Vibrio harveyi bacteria - Kannappan, Sudalayandi; Sivakumar, Krishnamoorthy; Sethi, Satyanarayan (Spanish Journal of Agricultural Research, 2018)
Application of chemicals for monitoring if Vibrio outbreaks can enhance resistance in mangrove (Rhizophora apiculata) leaves extract was tested against bioluminescence disease-causing Vibrio harveyi bacteria. An inhibitory zone of 12 mm was observed at 350 µg/mL The growth of V. harveyi was decreased from 0.783 to 0.533 (OD600) as compared to control (0.970 to 1.031 OD) against R. apiculata extract. The extract was treated against virulence produced by V. harveyi, the crude bacteriocin values decreased from 1.653 to 1.574 OD as compared with control. Further, extract 200 mg/mL was challenged against V. harveyi (10 mL at 1.8 OD600) during larviculture of Penaeus monodon for 30 days. The mortality increased from 9.0 to 68.5% in the control, but in the treatment the mortality varied from 0 to 57.8% till 30th day. The difference in the decrease of mortality in the treatments was 10.6%. V. harveyi count was decreased from 1.46 × 105 to 3 × 103 cfu/mL, respectively in the treatment for the 30th day as compared to control (1.33×105 to 9.2×103 cfu/mL). R. apiculata leaves extract was reported to have various functional groups of compounds as determined by Fourier Transform Infrared Spectroscopy (FTIR). The GC-MS analysis revealed that the R. apiculata extract contains compounds such as 1, 2-diacetate, cyclododecane, 2-chloropropionic acid and squalene. These compounds might be responsible for the antagonism against V. harveyi. Hence, crude extracts of R. apiculata can be used as a non-antibiotic agent to control shrimp disease caused by V. harveyi during larviculture.